Atividade citotóxica das frações, subfrações e annonacinona obtidos de sementes de Annona muricata L - Rocha, Gabriel Gusmão Grisi (2017)
The use of medicinal plants has been evidenced since the beginning to relieve and treat diseases and its use has grown over the years, constituting an important source in the therapeutic arsenal. The species Annona muricata, popularly known as soursop, is widely used as a traditional drug and studies conducted with its bioactive secondary metabolites have shown remarkable antitumor activity related to acetogenins. In this context, the present study aimed the bioguided fractionation of the acetonic extract of the A. muricata seeds to prospect for molecules with cytotoxic potential in human tumor cell lines, resulting in the isolation of an acetogenin called annonacinone. The study is a pioneer in the evaluation of the cytotoxic activity of the molecule. All fractions, subfractions and annonacinone presented cytotoxic potential in the tumor lines tested. The annonacinone showed IC50 values ranging from 3.7 μM to 0.19 μM in colon tumor cells (SW620) and glioblastoma (SF-295), respectively after 72 hours of incubation. The cytotoxic profile at different periods of incubation was performed on SF-295 cells and lung cells (NCI-H460). The cytotoxic effect on SF-295 cells was observed only after 72 hours of incubation, whereas in NCI-H460 cells, this effect was observed at 48 hours with IC50 of 0.21 μM and maintained after 72 hours of incubation. The temporal analysis of the cytotoxicity of annonacinone in NCI-H460 cells was evaluated by two different assays, MTT and SRB, which showed differences in the values, suggesting that the SRB assay is more effective for this kind of substance class because it depends on the protein content without interference of the compound. Annonacinone showed a decrease in cell density at all concentrations tested on NCI-H460 cells after 48 hours of incubation, although after this time of treatment it was not possible to evaluate DNA damage, cell cycle progression and cell death pattern. In an real-time analysis of the proliferation and viability, the annonacinone showed inhibition of the cellular growth in the tested concentrations and beginning of decline of the cellular index after 56 hours of treatment. It is concluded that acetogenin annonacinone presents evident cytotoxic activity in vitro, with greater effect in NCI-H460 cells, however, other tests should be performed with longer treatment times for a better evaluation of its biological activity and therapeutic potential of this molecule.